High-Resolution Infrared Spectroscopy of the v1 + v4 Band of 14NF3:Reductions of the Rovibrational Hamiltonian - Hamid Najib; Siham Hmimou; Hicham Msahal (E-Journal of Chemistry)
The high-resolution Fourier transform infrared spectrum of nitrogen trifluoride NF3 has been studied in the v1 + v4 perpendicular band region around 1523 cm−1. All experimental data have been refined applying various reduction forms of the effective rovibrational Hamiltonian developed for an isolated degenerate state of a symmetric top molecule. The v1 = v4 = 1 excited state of the 14NF3 oblate molecule was treated with models taking into account ℓ- and k-type intravibrational resonances. Parameters up to sixth order have been accurately determined and the unitary equivalence of the derived parameter sets in different reductions was demonstrated.